PEMBUATAN DAN ANALISIS BIO-ETANOL DARI PATI SAGU (Metroxylon sago) ASAL PAPUA - Bimo Budi Santoso; Dyah Novitasari; Prawatya Istalaksana (FMIPA Universitas Papua, 2010)
Preparation and bio-ethanol analysis of sago (M. sago) starch from Papua have been carried out. The preparation of bioethanol was conducted by hydrolysis, fermentation, distillation and purification. The length of fermentation applied is 3, 4, 5, 6, 7 and 8 days. Bioethanol then was analyzed qualitatively and quantitatively. Qualitative analyses were boiling point and molecular weight determination. Quantitative analyses were determination of the volume of bioethanol content and the composition of bioethanol of every length of fermentation. Based on the qualitative analyses, the samples obtained was ethanol with boiling point of 79 oC and molecular weight of 46 gram/mol. Whereas, based on the quantitative analyses, the more the length of fermentation, the more volume of ethanol obtained and the composition of ethanol increased, with the optimum of the fermentation length was 8 days and the volume ethanol obtained was 123.5 mL, in addition the composition of ethanol at fermentation length of 8 days was 100%.